Novel Approaches for Extracellular Matrix Targeting in Disease Treatment - Afratis, N. A.; Sagi, I. (Methods Mol Biol, 2019)
Extracellular matrix (ECM) macromolecules, apart from structural role for the surrounding tissue, have also been defined as crucial mediators in several cell mechanisms. The proteolytic and cross-linking cascades of ECM have fundamental importance in health and disease, which is increasingly becoming acknowledged. However, formidable challenges remain to identify the diverse and novel role of ECM molecules, especially with regard to their distinct biophysical, biochemical, and structural properties. Considering the heterogeneous, dynamic, and hierarchical nature of ECM, the characterization of 3D functional molecular view of ECM in atomic detail will be very useful for further ECM-related studies. Nowadays, the creation of a pioneer ECM multidisciplinary integrated platform in order to decipher ECM homeostasis is more possible than ever. The access to cutting-edge technologies, such as optical imaging and electron and atomic force microscopies, along with diffraction and X-ray-based spectroscopic methods can integrate spanning wide ranges of spatial and time resolutions. Subsequently, ECM image-guided site-directed proteomics can reveal molecular compositions in defined native and reconstituted ECM microenvironments. In addition, the use of highly selective ECM enzyme inhibitors enables the comparative molecular analyses within pre-classified remodeled ECM microenvironments. Mechanistic information which will be derived can be used to develop novel protein-based inhibitors for effective diagnostic and/or therapeutic modalities targeting ECM reactions within tissue microenvironment.
Afratis, Nikolaos ASagi, IritengReview2019/03/03Methods Mol Biol. 2019;1952:261-275. doi: 10.1007/978-1-4939-9133-4_21.
Keywords: *Biological inhibitors; *Cancer; *ECM targeting; *extracellular matrix; *Fibrosis; *inflammation; *Lysyl oxidases; *Matrix metalloproteases; Amino Acid Oxidoreductases/analysis/metabolism; Animals; Drug Discovery/methods; Extracellular Matrix Proteins/analysis/*metabolism; Extracellular Matrix/chemistry/drug effects/*metabolism/*pathology; Humans; Inflammation/drug therapy/metabolism/pathology; Neoplasms/drug therapy/metabolism/pathology; Protein-Lysine 6-Oxidase/analysis/metabolism; Proteolysis; Proteomics/*methods